ICHTYOFAUNA AT CIJALU RIVER, CILACAP REGENCY, CENTRAL JAVA PROVINCE, INDONESIA - Agus Nuryanto; Dian Bhagawati; M Nadjmi Abulias; Indarmawan Indarmawan (BIOTROPIA, 2016)
Cijalu River is located in the western part of Cilacap Regency, Central Java Province. The river flows through forestry, housing, and farming areas. These conditions lead to the prediction that its physico-chemical characteristics may have been altered, potentially affecting the fish species inhabiting the river. This study aimed to collect data on fish species inhabiting the Cijalu River and analyze their distribution. A survey method was conducted using a clustered random sampling technique. The river was divided into three sections: upstream, midstream, and downstream. Species diversity was measured based on the number of species recorded, while distribution was determined by the presence of fish species in each sampling site. Nineteen fish species belonging to ten families were identified from the Cijalu River. The ten families recorded were Anabantidae, Bagridae, Balitoridae, Channidae, Cichlidae, Cyprinidae, Loricariidae, Osphronemidae, Poecilidae, and Sisoridae. Cyprinidae represented the family with the highest number of species (6 species), followed by Channidae (3 species), Bagridae (2 species), and Osphronemidae (2 species). The remaining families were each represented by one species. Different patterns of fish distribution were observed during the study. Glyptothorax platypogon and Channa gachua were found only in the upstream area, while Anabas testudineus was collected only from the downstream section. Other species were found either from the midstream to downstream areas or throughout the entire river system. The variation in species distribution may be associated with changes in physico-chemical characteristics from upstream to downstream, particularly substrate type and water velocity.